2002
DOI: 10.1590/s0100-06832002000200007
|View full text |Cite
|
Sign up to set email alerts
|

Composição da solução de um solo alagado conforme a profundidade e o tempo de alagamento, utilizando novo método de coleta

Abstract: RESUMONa coleta da solução de solos alagados, é importante evitar o contato do oxigênio com a solução para prevenir reações redox que podem modificar sua composição química. Neste trabalho, realizado em casa de vegetação, foram feitos estudos sobre o estado de oxirredução e sobre a composição química de um Planossolo, em diferentes profundidades e tempos de alagamento, visando propor um novo método para a coleta da solução de solos alagados. O estudo foi feito em vasos plásticos com 7 kg de material de solo pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 1 publication
1
8
0
14
Order By: Relevance
“…In a study on different soil types, including an Albaqualf, Schoenfeld et al (2007) observed a sharp EC increase at depths of 5 and 10 cm 42 DIS, precisely because of the increased transpiratory demand in this period. Similar dynamics were observed by Sousa et al (2002), for K, Ca and Mg, 35 DIS. In rice cultivated in pots but with outflow of leachates, Chhabra & Abrol (1977) found a drastic reduction in the salinity of a highly salty soil, as in the present field study.…”
Section: Ion Dynamics In Soil Solution and Plant Uptakesupporting
confidence: 79%
“…In a study on different soil types, including an Albaqualf, Schoenfeld et al (2007) observed a sharp EC increase at depths of 5 and 10 cm 42 DIS, precisely because of the increased transpiratory demand in this period. Similar dynamics were observed by Sousa et al (2002), for K, Ca and Mg, 35 DIS. In rice cultivated in pots but with outflow of leachates, Chhabra & Abrol (1977) found a drastic reduction in the salinity of a highly salty soil, as in the present field study.…”
Section: Ion Dynamics In Soil Solution and Plant Uptakesupporting
confidence: 79%
“…These fertilizers were uniformly mixed to the soil of each pot. Soil solution extractors were installed at 5 and 10cm depth during pot filling, according to Sousa et al (2002). Four rice plants of cv.…”
mentioning
confidence: 99%
“…The pH and redox potential values (Eh) of the collected soil solution at 10cm were determined by combined specific electrodes, according to Sousa et al (2002). Also, 30mL of soil solution were collected at 5 and 10cm depths for determining ammonium (NH 4 + ) and nitrate (NO 3 -) concentrations by steam destillation, with the help of a Kjeldahl distiller (TEDESCO et al, 1995).…”
mentioning
confidence: 99%
“…18 Nas colunas de solo na condição de saturação, verifica-se que com o tempo de alagamento ocorreu uma queda e posterior estabilização nos valores de Eh a valores abaixo de -200 mV, sendo considerada uma condição de severa redução. De acordo com a literatura, 6,19,20 nesse valor de Eh já poderá ocorrer a redução do sulfato a sulfeto pelas bactérias (BRS) presentes no solo. O receptor de elétrons, que antes era o O 2 , passa a ser outros componentes inorgânicos que serão reduzidos.…”
Section: Resultsunclassified